Quandaries in Air Cargo Handling and Its Effect on Truck Turnover Time (International Journal of Psychosocial Rehabilitation, 2020)
Air cargo has been facing tremendous challenges on various dimensions, right from equipment, transportation, manpower, emissions, freight cost, fuel cost, etc. The paper aims at finding the challenges related to handling air cargo services and its effect on the turnover time. An empirical study was conducted using a purposive sampling technique with a structured survey questionnaire. The respondents were truck drivers of cargo and ground staff of cargo allied services. The study was conducted in one of the air terminals in the southern part of India. The findings of the analysis infer that the major challenges are a shortage of manpower and a shortage of scanning and weighing equipment at the terminal. Experienced cargo truck drivers were found to have fewer challenges than the less experienced. The management should employ more experienced truck drivers and also consider the shortage of manpower and equipment to improve their service efficiency.